Musculoskeletal Disorders among Traditional Bangladeshi Fishermen - Mohammed Emran; Md Israt Hasan; Taufiq Morshed; Syed Mozaffar Ahmed (KYAMC Journal, 2023)
Background: Fishing is one of the most important economic activities in riverine Bangladesh. We studied musculoskeletal disorders (MSDs) among Bangladeshi fishermen which is generally high. Objective: To study patterns and extend of MSDs among Bangladeshi fishermen. Materials and Methods: A total 150 fishermen enrolled with at least six months employment history attended at out-patient department of Physical Medicine and Rehabilitation of Khwaja Yunus Ali Medical College and Hospital of Sirajganj district, Bangladesh, in this cross-sectional study using a random sampling procedure. The Nordic Questionnaire was used to assess work-related musculoskeletal disorders. To determine the significance of age, BMI and working experience with pain and discomfort in different regions of the body, Pearson Correlation test was done. Results: Musculoskeletal disorder among fishermen due to extreme physical demand during the hauling of fishing nets on the raft in Jamuna River and its tributaries with the prevalence significantly higher. All body region were affected by musculoskeletal problems, among them the highest prevalence found in lower back and lowest in upper back (37.3%) region. There were significant associations of age with wrist pain (P=0.039), lower back pain (0.025) and knee pain (0.021). There was no significant association of BMI with any pain or discomfort. Total working experience of fishermen had significant association with pain or discomfort within last 12 months in shoulder (p=0.008), wrist (0.023), lower back (0.022) and knee (0.001). Conclusion: Long hours of fishing in a traditional fishing boat with age-old equipments adopting inconvenient ergonomic posture can lead high prevalence of musculoskeletal problems among fishermen. KYAMC Journal Vol. 14, No. 01, April 2023: 11-15